The Application of Chicken Manure Fertilizer on the Growth and Yield of Shalot (Allium ascalonicum L.) Plants of the Tajuk Variety in a Floating System - Susilawati, Susilawati; Haqqi, Verza Dharma; Irmawati, Irmawati (Seminar Nasional Lahan Suboptimal, 2024)
Susilawati, S., Haqqi, V. D., & Irmawati, I. (2024). The application of chicken manure fertilizer on the growth and yield of shalot (Allium ascalonicum L.) plants of the tajuk variety in a floating system. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-12 Tahun 2024, Palembang  21 Oktober 2024. (pp. 799–816).  Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Shallots are one of the plants that produce economically valuable bulbs that can becultivated conventionally or with a floating farming system. The purpose of this study was to determine the impact and best dosage of providing variations in chicken manure fertilizer with a floating system on the growth and yield of shallots (Allium ascalonicum L.) tajuk variety. This research was conducted at the Embung Faculty of Agriculture, Sriwijaya University with coordinates 003 ° 13'16 "LS and 104 ° 39'03" BT in July to August 2024. The study was conducted using a Randomized Block Design (RAB) consisting of 4 treatments and 3 replications. The variation of fertilizer doses used in this study were P0 = Control (Without chicken manure fertilizer), P1= 10 Tons/ha (40 grams of chicken manure fertilizer/polybag, P2= 20 Tons/ha (80 grams chicken manure fertilizer/polybag), P3 = 30 Tons/ha (120 grams of chicken manure fertilizer/polybag). The parameters observed were plant height, number of leaves, leaf area, leaf greenness level per week, leaf greenness level per hour, leaf growth age, fresh weight of shoots, dry weight of shoots, number of tillers, number of bulbs, bulb length, bulb diameter, bulb volume, fresh bulb rice, air dried of bulb weight, and root length. The results of the study showed that variations in the dose of chicken manure fertilizer did not have a significant effect on the growth and yield of shallots planted in a floating system. Even so, a dose of 10 tons/ha or 80 grams/polybag (P2) produced better growth and production than other treatment.